2008
DOI: 10.1007/s00198-008-0601-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-and region-dependent changes in three-dimensional microstructural properties of proximal femoral trabeculae

Abstract: Age-related changes in bone loss and trabecular microstructure within the male proximal femur are not uniform in this cadaveric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
7
38
1
Order By: Relevance
“…Therefore it is more brittle and more likely to fracture. Conn.D decreases significantly with age [49,50] . When the trabecular bone volume fraction declines, Conn.D will decline concomitantly, probably because of small trabecular bone loss [25,49] .…”
Section: Femoral Neckmentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore it is more brittle and more likely to fracture. Conn.D decreases significantly with age [49,50] . When the trabecular bone volume fraction declines, Conn.D will decline concomitantly, probably because of small trabecular bone loss [25,49] .…”
Section: Femoral Neckmentioning
confidence: 93%
“…There have been many studies conducted to investigate the underlying causes of femoral neck fracture. It is suggested that 3D microstructures play a significant role in assessing the bone quality and provide compelling evidence to explain the bone strength [48][49][50] . The proximal femur was isolated by cutting at the base of femoral head and femoral neck.…”
Section: Femoral Neckmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent study examined the microstructural differences in femoral neck trabecular bone between hip fracture patients and controls, and confirmed significant decrease in bone volume fraction and a transition from plate-like to rod-like trabeculae in hip fracture patients (12). However, microstructural and biomechanical changes associated with intertrochanteric fractures have not been studied, and cannot be derived from the previous femoral neck studies due to heterogeneous trabecular bone distribution in the proximal femur (13)(14). Also, Li et al suggested that location of hip fracture was most strongly associated with the vBMD near the site of fractures in femoral neck and intertrochanteric region (15).…”
Section: Introductionmentioning
confidence: 98%
“…The weak correlation with age may indicate that an alteration of macroscopic mechanical competence of the proximal femur is associated with bone fragility (McCalden et al, 1993;Homminga et al, 2002) and is due to structural changes such as an decline in trabecular thickness and number (Cui et al, 2008;Djurić et al, 2012) and is not accompanied by the decreasing mechanical properties of trabecular bone at the microlevel. Nevertheless, it has been reported that the mechanical properties of bone tissue as measured by nanoindentation correlate to bone tissue age, which is associated with the degree of mineralization and bone remodelling.…”
mentioning
confidence: 99%